Воєнізація в міліції УСРР на початку 20-х років ХХ сторіччя - Галкін, Д. В.; Halkin, D. V.; ORCID: http://orcid.org/0000-0001-7247-1037 (Право і безпека. - 2013. - № 2 (49). - С. 23-29, 2013)
Розглянуто вплив процесу воєнізації міліції УСРР на початку 1920-х рр. на стан правоохоронних органів України. Відзначаючи, що воєнізація допомогла у вирішенні низки важливих проблем, у той же час звернуто увагу на певні недоліки, усунення яких вимагало продовження подальшої реорганізації органів внутрішніх справ, пристосування їх до роботи в нових умовах, пов’язаних із запровадженням НЕПу.

Beginning of 1920-s was a period of testing the strength of the new Soviet authority system. Its vitality is not in the last place dependent on the law enforcement agencies’ state. Categorical refusal of the workers’ and peasants’ militia (police) inheriting achievements of the tsarist police was typical for this time that reduced an organization of law and order protection of the young Soviet state to zero. Personnel policy in the internal affairs was determined by method of attempts and mistakes. In such circumstances one of the key factors that allowed to keep the new internal affairs agencies as a managed power and system was the orientation on military model. Just under the influence of militarization new law enforcement system was fundamentally formed. The system’s certain features were preserved in the Soviet militia (police) during the whole period of its existence and were borrowed by the police of modern Ukraine, as well as by other post-Soviet states. Since middle of 1921 militia (police) began the process of militarization – conscious reorganization of militia (police) after the military model with simultaneous subordination to the military command in matters solely combatant training and supplies. The main purpose of militarization was to discipline, to teach military service, to unite to the military associations, to rearm of the same type of weapons and to provide with the necessities. One of the features of militarization was the restructuring of militia (police) – supplementing the structure of military drill parts that undoubtedly would improve mobility and increase discipline in the militia (police). The result of militarization was the necessity of creating another structure of power, which would execute the part of functions stiffly executed by militia (police). This structure became the State Political Administration.

Рассматрено влияние процесса военизации милиции УССР в начале 1920-х гг. на состояние правоохранительных органов Украины. Отмечая, что военизация помогла в решении ряда важных проблем, в то же время обращено внимание на некоторые недостатки, решение которых требовало дальнейшей реорганизации органов внутренних дел, приспособления их работы к новым условиям, связанными с внедрением НЭПа.
Militarization of Ukrainian Socialist Soviet Republic’s militia (police) in the early 20-s of the XX century
Военизация в милиции УССР в начале 20-х годов ХХ века
Галкін, Д. В. Воєнізація в міліції УСРР на початку 20-х років ХХ сторіччя / Д. В. Галкін // Право і безпека. - 2013. - № 2 (49). - С. 23-29.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Історія. History. История; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; органы внутренних дел; Internal Affairs Agencies; міліція; милиция; militia; воєнізація; военизация; militarization